PERAN YOUTUBE TERHADAP PEMBENTUKAN NILAI MORAL DAN KARAKTER ANAK USIA DINI - Ahmad Hariandi , Ajeng Aura Nurlillahi, Anggun Marta Rena, Hasna Nurjilan, Orbit Junita (Jurnal Pendidikan Pemuda Nusantara, 2020)
The purpose of this research to know what part YouTube in the formation of moral and the value of a character in early childhood with a target of the subject are located in Jambi, Jambi Province .The subject of consisting of 7 children with the age range of the subject between 3-8 years, the elections based on liveliness of the children in access YouTube itself. Data collection during technique was used in the study non-participant observation, the survey or non-structured quisioner and interview non-structured. This research result indicates that the role of parents it is important in driving spectacle able to provide education for children.